Examining Child Welfare Decisions and Services for Asian-Canadian Versus White-Canadian Children and Families in the Child Welfare System. (May 2017) - Lee, Barbara; Fuller-Thomson, Esme; Fallon, Barbara; Black, Tara; Trocmé, Nico
Using administrative child welfare data from the Ontario Child Abuse and Neglect Data System (OCANDS), this study compared the profiles of Asian-Canadian and White-Canadian children and families that experienced a case closure after an investigation instead of being transferred to ongoing child protection services (CPS). Child protection investigations involving Asian-Canadian and White-Canadian children and families that were transferred to ongoing CPS presented a different profile of case characteristics and caregiver and child clinical needs. Asian-Canadian children and families received ongoing CPS for over a month longer than White-Canadian children and families and were less likely (odds ratio [ OR ] = 0.39) to be reinvestigated for any form of maltreatment-related concerns within 1 year after case closure. It appears that child protection investigations involving Asian-Canadian children and families are less likely to be closed prematurely than White-Canadian children and families, and the child protection system may be meeting the needs of Asian-Canadian communities. Alternatively, it is possible there is unaccounted biases that may be reflective of systemic problem of discriminative practices in the child protection system. Further research is needed to explore this phenomenon.